The Role of Microvascular Density (MVD) in Cervical Cancer: A Article Review - Winata, I Gde Sastra; Aryana, Made Bagus Dwi; Marta, Kadek Fajar; Christyani, Fenyta (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: The development, invasion and metastasis process of cervical cancer is closely related to the ability of cancer cells in the process of tumor oxygenation and the process of angiogenesis. Angiogenesis plays a very important role in the growth, metastasis and progression of tumor cells. Microvascular Density (MVD) is an examination that counts the number of microvasculature compared to the area of tissue analyzed by histology and immunohistochemistry. Method: This study reviewed literature by searching the Pubmed, ScienceDirect, and Cochran Library Database. The search query included “microvascular” and “cervical cancer”. The study was reviewed using the Preferred Reporting Item for Systemic Reviews and Meta-Analyses (PRISMA) standards. The scope of analysis was restricted to clinical trials conducted from 2011 to 2023Result: Currently, MVD examination is an examination that is often carried out to evaluate the process of intratumor angiogenesis in cancer. By knowing the MVD value in cancer sufferers, it is hoped that it can be considered in determining therapy and assessing the outcome of the course of cervical cancer which can be considered as a prognostic factor. Apart from that, it can complement the theory of other biomolecular prognostic factors that play a role in cervical cancer such as vascular endothelial growth factor (VEGF), Ki-67 protein, p53 tumor suppressor gene, oxygenation factors, especially hypoxia inducible factors-1α (HIF-1α), enzymes protease (matrix metalloproteinase), and cell adhesion molecules (E-Kadherin, catenin).Conclusion: The role of MVD in cervical cancer sufferers as an indicator of prognosis and success of therapy.Peranan Kepadatan Mikrovaskuler (MVD) pada Kanker Serviks: Sebuah Ulasan ArtikelAbstrakPendahuluan: Proses perkembangan, invasi dan metastasis kanker serviks erat kaitannya dengan kemampuan sel kanker dalam proses oksigenasi tumor dan proses angiogenesis. Angiogenesis memainkan peran yang sangat penting dalam pertumbuhan, metastasis, dan perkembangan sel tumor. Kepadatan Mikrovaskular (MVD) merupakan pemeriksaan yang menghitung jumlah mikrovaskular dibandingkan dengan luas jaringan yang dianalisis secara histologi dan imunohistokimia. Metode: Pencarian literatur dilakukan pada database PubMed dan ScienceDirect dan Cochrane Library. Pencarian dilakukan menggunakan istilah “mikrovaskular” dan “kanker serviks”. Penulisan sistematik review disesuaikan dengan pedoman Professed Reporting for Systematic Review and Meta-Analysis (PRISMA). Semua studi yang diinklusi merupakan uji klinis pada periode tahun 2011 – 2023.Hasil: Saat ini MVD merupakan pemeriksaan yang sering dilakukan untuk mengevaluasi proses angiogenesis intratumor pada kanker. Dengan mengetahui nilai MVD pada penderita kanker diharapkan dapat menjadi pertimbangan dalam menentukan terapi dan menilai luaran perjalanan penyakit kanker serviks yang dapat diperhitungkan sebagai faktor prognosis. Selain itu dapat melengkapi teori faktor prognostik biomolekuler lain yang berperan dalam kanker serviks seperti faktor pertumbuhan endotel vaskular (VEGF), protein Ki-67, gen penekan tumor p53, faktor oksigenasi, terutama faktor pemicu hipoksia-1 α (HIF-1 α), enzim protease (matrix metalloproteinase), dan molekul adhesi sel (E-Kadherin, catenin).Kesimpulan: MVD pada penderita kanker serviks berperan sebagai indikator prognosis dan keberhasilan terapiKata kunci: Kepadatan vaskular, kanker serviks, diagnosis